''Effectiveness of Non-invasive Positive Pressure Ventilation in ELBW Infants: A Comparison of Successful and Failed Outcomes'' - Ratheesh Paramban (17046388) (2023)
Background  Premature infants, particularly those with extremely low birth weight (ELBW), are at a higher risk of respiratory distress syndrome (RDS) and associated complications. Non-invasive positive pressure ventilation (NIPPV) has become an increasingly popular mode of respiratory support for these infants. However, it remains unclear which ELBW infants are best suited for NIPPV and what factors may contribute to success or failure of this mode of ventilation. Objective This retrospective study aim to evaluate the effectivemness of NIPPV by comparing the success rate and outcomes of ELBW infants who were successfully managed with NIPPV to those who failed NIPPV support. The results of this study may provide insight into the effectiveness of NIPPV in this vulnerable population and inform clinical decision-making regarding respiratory support for ELBW infants. Design and methodology The study was conducted retrospectively at the Women’s Wellness and Research Center in ELBW infants who received respiratory support with NIPPV between 2015 and 2019. The study included a total of 181 ELBW infants, out of which 79 were intubated in the delivery room and 43 were placed on Continuous Positive Airway Pressure (CPAP) support. The remaining 69 infants satisfied the criteria for primary NIPPV analysis. The primary goal of the study was to determine the NIPPV success and failure rates ( NIPPV-S/NIPPV-F) and compare various clinical outcomes between the groups. The study analyzed various parameters such as duration of NIPPV support, arterial Ph, Fio2 requirement, chest X-ray findings and incidence of brain injury and broncho pulmonary dysplasia. Results Out of the 69 infants who received primary NIPPV support, 26 infants (38%) did not pass the 24-hour period criteria and required intubation and mechanical ventilation. The mean birth weight and gestational age were 968 grams and 26.4 weeks, respectively, with a higher percentage of vaginal births in the NIPPV-success group compared to the NIPPV-failure group (48.8 % vs 19.2 %, p=0.014). The duration of NIPPV support was significantly longer in the NIPPV-success group compared to the NIPPV-failure group (mean 36+_27.6 hours vs 9.4+_21.3 hours, p<0.001), 2 babies in the NIPPVS we later intubated at mean 209 hours vs 9.4 hours in the NIPPV-F group, due to increased work of breathing and FiO2 requirement. The NIPPV-Failure group had lower arterial pH and high FiO2 requirements in the delivery room (7.29 vs 7.36, p<0.001, and 28% vs 34%, p<0.001, respectively). Chest X-ray findings of severe RDS were significantly lower in the NIPPV-success group (2.5% vs 28.6%). More babies in the NIPPV-success group were on room air at 28 days of age (30.2% vs 4.2%, p=0.016) and at 36 weeks postmenstrual age (81.4% vs 58.3%). The incidence of brain injury (any IVH and PVL) was significantly lower in the NIPPV-success group (15% vs 45.8%, p=0.007). Finally, the NIPPV-success group had a significantly lower incidence of death or severe bronchopulmonary dysplasia compared to the NIPPV-failure group (2.3% vs 15.4%, p=0.043). Regression analysis results suggest that four factors are significantly associated with failed NIPPV. These include FiO2 upon NICU admission (p=0.007, adjusted odds ratio (aOR) =1.153, 95% CI=1.041-1.278), abnormal fetal Doppler (p=0.048, aOR=8.714, 95% CI=1.018-74.620), Cesarean delivery (p=0.024, aOR=6.039, 95% CI=1.266-28.812), and pH value (p=0.037, aOR=0.000, 95% CI=0.000-0.422). Conclusions  NIPPV appears to be an effective respiratory support option for ELBW infants, with a success rate of 62%. The NIPPV-success group had a longer duration of support, but had better outcomes, with lower incidence of severe RDS, brain injury, and death or severe BPD. These findings can be used to identify high-risk neonates who may benefit from early intervention to prevent or treat failed NIPPV. However, further studies are needed to confirm these findings and explore the underlying mechanisms of these associations.